Piękno a zdrowie. Krytyka kosmetyki w dyskursie higienicznym drugiej połowy XIX w. - Napierała, Anita (W zwierciadle rzeczy, 2022)
The development of cosmetic trade and industry in the second half of 19th century aroused the interest of hygienists and doctors in the health effects of cosmetics. The usefulness and effectiveness of cosmetic products, their application, methods of production and sales caused a lot of controversy. The controversy arose mainly from the belief that advertised cosmetics are not healthy but were produced for profit, by manufacturers who did not possess proper knowledge. The article discusses the views and opinions on cosmetics contained in Polish periodicals and health and hygiene advice books from the second half of the nineteenth century. The arguments of hygiene advocates are discussed in the context of the nineteenth-century aesthetic concepts of the body, the related standards of male and female beauty and their relation to the then popular hygienic postulates of health prophylaxis.